Hardware implementation of pi/4-DQPSK modem for mobile communication (Short Communication) - Bhat, K.P.M.; Jogdand, Saurabh; Malshe, Salil; Kelkar, Vasundhara (Defence Science Journal, 2002)
Spectrally efficient digital modulation schemes for land mobile voice transmission applications highlighting advantages of a 7Pi/4-DQPSK modem are briefly reviewed, A procedure to generate 7Pi/4-DQPSK signal by directly mapping pairs of input bits through dibit transformation function and analog multiplexer is described. Details of modulator hardware for a standard data rate of 48 kbps are also incorporated, A promising all-digital receiver structure which lends itself for miniaturisation, is described.